Genetic polymorphism in Methylenetetrahydrofolate Reductase chloride transport protein 6 (MTHFR CLCN6) gene is associated with keratinocyte skin cancer in a cohort of renal transplant recipients - L. Griffin; L. Ho; R. J. Akhurst; S. T. Arron; J. M. E. Boggs; P. Conlon; P. O'Kelly; A. E. Toland; E. H. Epstein; A. Balmain; B. C. Bastian; F. J. Moloney; et al. (Wiley, 2022)
Abstract Background Renal transplant recipients (RTRs) are at increased risk of keratinocyte cancer (KC), especially cutaneous squamous cell carcinoma (cSCC). Previous studies identified a genetic variant of the Methylenetetrahydrofolate Reductase (MTHFR) gene, C677T, which conferred a risk for diagnosis of cSCC in Irish RTRs. Objective We sought to find further genetic variation in MTHFR and overlap genes that may be associated with a diagnosis of KC in RTRs. Methods Genotyping of a combined RTR population (n = 821) from two centres, Ireland (n = 546) and the USA (n = 275), was performed. This included 290 RTRs with KC and 444 without. Eleven single nucleotide polymorphisms (SNPs) in the MTHFR gene and seven in the overlap gene MTHFR Chloride transport protein 6 (CLCN6) were evaluated and association explored by time to event analysis (from transplant to first KC) using Cox proportional hazards model. Results Polymorphism at MTHFR CLCN6 (rs9651118) was significantly associated with KC in RTRs (HR 1.50, 95% CI 1.17-1.91, p < 0.00061) and cSCC (HR 1.63, 95% CI 1.14-2.34, p = 0.007). A separate SNP, MTHFR C677T, was also significantly associated with KC in the Irish population (HR 1.31, 95% CI 1.05-1.63, p = 0.016), but not American RTRs. Conclusions We report the association of a SNP in the MTHFR overlap gene, CLCN6 and KC in a combined RTR population. While the exact function of CLCN6 is not known, it is proposed to be involved in folate availability. Future applications could include incorporation in a polygenic risk score for KC in RTRs to help identify those at increased risk beyond traditional risk factor assessment.